Immigration concern and the white/non-white difference in smoking: Group position theory and health - Frank L. Samson (Elsevier, 2017)
National data indicate that U.S. whites have a higher prevalence of smoking compared to non-whites. Group position theory and public opinion data suggest racial differences in immigration concern. This study examines whether immigration concern mediates the racial difference in smoking. Drawing on the 2012 General Social Survey, the 2012 American National Election Study, and the 2006 Portraits of American Life Study, immigration concern was associated with smoking, controlling for covariates across all three nationally representative surveys. Mediation analysis indicated that immigration concern partially mediated the higher odds of smoking among whites across all surveys. Immigration concern also presents a possible explanation for the healthy immigrant advantage and Hispanic paradox as they pertain to smoking differences.